Evidence-Based Network Modelling to Simulate Nucleus Pulposus Multicellular Activity in Different Nutritional and Pro-Inflammatory Environments - Baumgartner, L.; Sadowska, A.; Tío, L.; González Ballester, M. A.; Wuertz-Kozak, K.; Noailly, J. (Frontiers in Bioengineering and Biotechnology, 2021)
Initiation of intervertebral disc degeneration is thought to be biologically driven, whereby small persistent changes in cell activity (CA) compromise the tissue strength over time. Biochemical key stimuli such as glucose, pH, and the proinflammatory cytokines TNF-α and IL1β were shown to contribute to this process. This work presents an interdisciplinary approach of experimental and in silico research to approximate Nucleus Pulposus CA within multifactorial biochemical environments, leading to the prediction of different proinflammatory cell status (CS). To this end, a Nucleus Pulposus multicellular system was modelled, and the individual effect of each targeted stimulus was related to alterations in CA, as determined through changes in the mRNA expressions of Aggrecan, Collagen types I & II, MMP3, and ADAMTS4. Unknown stimulus-CA relationships were obtained experimentally through 3D cultures of bovine Nucleus Pulposus cells in alginate beads. Integration of experimental findings into the model was achieved thanks to a new numerical approach developed to estimate the individual sensitivity of a CA to each stimulus type. Eventually, cell behavior in multifactorial environments was predicted in a multicellular 3D agent-based model, in which the different proinflammatory CS were estimated through network-based integration. Experimental results showed that glucose had no significant impact on proinflammatory cytokine or ADAMTS4 mRNA expression, whereas TNF-α caused a significant catabolic shift in most explored CA. In silico predictions showed that an integration of the sensitivity of CA to a type of stimulus, improved approximations of experimental findings. Results indicate, however, that more stimuli and/or further experimental knowledge need to be integrated, especially regarding the possible progression of inflammatory environments under adverse nutritional conditions. Approaches at the multicellular level are promising to estimate the CA of cells exposed to a multifactorial environment. This includes indications towards incorrect or incomplete stimulus environments for a certain CA. Within this work, a systematic in silico approach determined the need for experimental research. The biological information obtained was then directly used to enhance model predictions. Results suggest that such an interdisciplinary approach through close collaboration between experimental and in silico research lines will help unravelling biologically derived injury mechanics.